Contrasting Learning Psychology Theories Applied to the Teaching-Learning-Training Process of Tactics in Soccer - Hallé Petiot, Grégory; Aquino, Rodrigo; Silva, Davi Correia da; Barreira, Daniel Vieira; Raab, Markus (Frontiers in Psychology, 2021)
Research in sport pedagogy and its applied recommendations are still characterized by a contrast between the different learning theories from psychology. Traditional theories and their corresponding approaches to the specific case of teaching and learning “how to play [team sports like soccer]” are subject to compatibilities and incompatibilities. We discuss how behaviorism as an approach to teaching the game shows more incompatibilities with the na-ture of tactical actions when compared to constructivism. As coaches strive to teach the game and make their players and team perform, we argue that teaching the game requires teaching approaches that will help develop their way to play (i.e., the tactical behavior) without taking away their autonomy and adaptiveness. The teaching-learning-training process for playing the game should then be conducted to harmonize the characteristics of the contents, the context and the individual(s) at hand. We provide two illustrated examples and portray how the rec-ommended approaches fit key contents of the game that are observed in the tactical behavior. We finally argue that the coherent design of games provides minimal conditions to teaching approaches, and that such design should be a priority when elaborating the learning activities along the player development process. As a conclusion, the interactionist theory is the one that best serves the teaching of the game and the development of tactical behavior. We there-fore defend that its principles can help coaches tailor their own strategy to teach the game with the many tools to teach the game.